2006
DOI: 10.1159/000093896
|View full text |Cite
|
Sign up to set email alerts
|

Average Years of Potential Life Lost in Those Who Have Died from Brain and CNS Tumors in the USA

Abstract: The aim of this study was to quantify the impact of all primary malignant and nonmalignant brain and central nervous system (CNS) tumors on mortality in the USA in terms of years of life lost, an indicator of premature mortality in the population. In this study, US mortality data for the year 2001 from the National Center for Health Statistics and life tables from the US Census Bureau were used. Person-years of potential life lost (PYPLL) and average years of potential life lost (AYPLL) were calculated for all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
4
9
0
Order By: Relevance
“…Consistent with those in previous publications [8, 9, 17, 18], the findings of the current analysis show that, on average, people with CNS cancer lost as many as 23 years of life among men and 27 years among women in 1980. Although their lifespan was prolonged in recent years, patients with CNS cancers still lost 21 years of life among men and 23 years among women in 2010.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with those in previous publications [8, 9, 17, 18], the findings of the current analysis show that, on average, people with CNS cancer lost as many as 23 years of life among men and 27 years among women in 1980. Although their lifespan was prolonged in recent years, patients with CNS cancers still lost 21 years of life among men and 23 years among women in 2010.…”
Section: Discussionsupporting
confidence: 92%
“…Although their lifespan was prolonged in recent years, patients with CNS cancers still lost 21 years of life among men and 23 years among women in 2010. Burnet et al [17] reported in their study of United Kingdom data [9] from 1990 to 1994 that patients with CNS cancers lost an average of 20 years of life, which was the largest loss among any types of cancers. Thuppal et al [9] used US 2001 data and reported an average loss of 21.3 years for CNS cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ependymal tumours are neuroectodermal tumours that although rare have a significant impact on the quality of life and mortality (Thuppal et al , 2006). These tumours are derived from ependymal cells that line cerebrospinal fluid (CSF)-filled ventricles, spinal canal and filum terminale (Del Bigio, 1995).…”
mentioning
confidence: 99%